2007
DOI: 10.1016/j.juro.2007.03.194
|View full text |Cite
|
Sign up to set email alerts
|

Urachal Anomalies: A Longitudinal Study of Urachal Remnants in Children and Adults

Abstract: Urachal anomalies present and progress differently in pediatric and adult populations. Adults are at high risk for urachal cancer but children usually incur lower morbidity. Urachal lesions noted early in childhood should be excised to prevent problems in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
0
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(152 citation statements)
references
References 20 publications
1
140
0
11
Order By: Relevance
“…Adult patients with urachal anomalies should undergo an abdominal CT scan because of the high risk of malignancy of up to 25%. Ashley et al reported the increased risk of malignancy of a cystic urachal mass with increasing age [9]. In their study, 20% of patients with urachal cancer presented with metastatic disease.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Adult patients with urachal anomalies should undergo an abdominal CT scan because of the high risk of malignancy of up to 25%. Ashley et al reported the increased risk of malignancy of a cystic urachal mass with increasing age [9]. In their study, 20% of patients with urachal cancer presented with metastatic disease.…”
Section: Discussionmentioning
confidence: 90%
“…agnosis [9]. Herein, we report our initial experience of 4 cases of RLPC performed on urachal diseases and evaluate the perioperative and pathologic results.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults with persistant urachus 66% had hematuria or pain and 90% underwent excision. Surgical treatment in children consisted of simple excision, whereas over 50% of adults required partial or radical cystectomy because of malignancy [4] . A recent report showed that children are more likely to have an infected urachal cyst, while adults are more likely to have an infected urachal sinus [5] .…”
Section: Discussionmentioning
confidence: 99%
“…If urachal remnants are not removed in childhood and they are observed, exposure to chronic urinary stasis, infection and inflammation in the remnant may predispose the patient to potentially lethal malignancy. 10 The relative frequency of these lesions in six case series of 184 children with urachal anomalies is shown in Table 1. The precise incidence of an urachal remnant herniating into the umbilical cord (Figure 3b) is not described in the literature.…”
Section: Discussionmentioning
confidence: 99%